Effect of Mocaf Tempeh Date Biscuit on the Nutritional Status of Wasted and Stunted Toddlers - Fatmah (Pakistan Journal of Nutrition, 2017)
Background and Objective: The poor nutritional status of wasted and stunted toddlers can decrease their cognitive development and growth. This study aimed to assess the effects of the consumption of modified cassava flour tempeh date biscuits on the nutritional status of wasted, stunted and wasted-stunted toddlers. Materials and Methods: This study used a quasi-experimental design with purposive sampling included 50 toddlers who consumed 50 g of biscuits within 90 days. Results: The toddlers’ means weight increased by 0.2 kg and their height increased by 1.9 cm. The intake of energy, protein and fat resulted in a change in the nutritional status of short toddlers, who reached normal height (p<0.05). Conclusion: Modified cassava flour tempeh date biscuit supplementation can decrease the prevalence of stunting in toddlers.